In Campylobacter jejuni, a new type of chaperone receives heme from ferrochelatase - Jordi Zamarreño Beas; Marco A. M. Videira; Val Karavaeva; Frederico M. Lourenço; Mafalda R. Almeida; Filipa Sousa; Lígia M. Saraiva (Frontiers in Genetics, 2023)
Intracellular heme formation and trafficking are fundamental processes in living organisms. Bacteria and archaea utilize three biogenesis pathways to produce iron protoporphyrin IX (heme b) that diverge after the formation of the common intermediate uroporphyrinogen III (uro’gen III). In this study, we identify and provide a detailed characterization of the enzymes involved in the transformation of uro’gen III into heme in Campylobacter jejuni, demonstrating that this bacterium utilizes the protoporphyrin-dependent (PPD) pathway. In general, limited knowledge exists regarding the mechanisms by which heme b reaches its target proteins after this final step. Specifically, the chaperones necessary for trafficking heme to prevent the cytotoxic effects associated with free heme remain largely unidentified. In C. jejuni, we identified a protein named CgdH2 that binds heme with a dissociation constant of 4.9 ± 1.0 µM, and this binding is impaired upon mutation of residues histidine 45 and 133. We demonstrate that C. jejuni CgdH2 establishes protein–protein interactions with ferrochelatase, suggesting its role in facilitating heme transfer from ferrochelatase to CgdH2. Furthermore, phylogenetic analysis reveals that C. jejuni CgdH2 is evolutionarily distinct from the currently known chaperones. Therefore, CgdH2 is the first protein identified as an acceptor of intracellularly formed heme, expanding our knowledge of the mechanisms underlying heme trafficking within bacterial cells.